Carbon Footprint of Recycled Aggregate Concrete. (30th May 2018) - Jiménez, Luis F.; Domínguez, José A.; Vega-Azamar, Ricardo Enrique
Abstract : Carbon footprint is one of the most widely used tools for assessing the environmental impacts of the production and utilization of concrete as well as of the components derived from it, representing the amount of carbon dioxide and other greenhouse gases associated with this product, expressed as CO2 equivalents. In this paper, carbon footprint was used to compare the environmental performance in the production phase of a concrete made with both recycled and crushed virgin limestone aggregates, using a life cycle analysis methodological approach. Research outcomes revealed, as expected, that carbon dioxide equivalent emissions decreased slightly as the use of recycled aggregates increased. Emissions for concrete with 0.5 w/c were between 347 and 351 kg of CO2 - e /m 3 . It was also corroborated that cement is the material with the greatest influence on greenhouse gas emission generation in the concrete's production phase, regardless of the use of recycled or virgin aggregates.